CATUR EMPATI (CEMPA) : An Innovative Educational Game Approach to Enhance Empathy and Prevent Bullying - Shofa Fadhilah Hidayat; Mudiyah Nasiriyah; Endang Herawan; Iis Yeni Sugiarti (Jurnal Educative: Journal of Educational Studies, 2025)
Low empathy in students is a major factor significantly driving the emergence and continuation of bullying behavior in the school environment. This study aimed to measure the effectiveness of the empathy chess educational game (catur empati – Cempa ) in increasing empathy of elementary school students, analyzing the impact of Cempa on reducing physical and verbal bullying in the elementary school environment. This research employed a mixed methods approach with an explanatory sequential design. The data collection techniques included pretests-posttests, interviews, and questionnaires. The data analysis technique in this study used the N-Gain test from the pretest-posttest results and triangulation from the results of interviews and questionnaires. The results in this study show the effectiveness of the Cempa in increasing student empathy through pretest and posttest. The average N-Gain value on empathy knowledge and empathy attitudes is classified as a moderate category. Meanwhile, the average N-Gain value in the aspect of empathy action is classified as a low category. The impact of the educative game Cempa on physical and verbal bullying is also seen to have decreased bullying behavior. This is due to the level of empathy, knowledge, and attitudes of students who have increased after playing Cempa. So, it is proven that the Cempa can increase empathy to reduce bullying behavior